Kunst und Zeremoniell in Rom während des Pontifikates unter Paul V. (1605-1621) Die Festapparate der Heiligsprechungen Francesca Romanas und Carlo Borroemoes in St. Peter und die Sala Regia im Quirinalspalast - Bodenstein, Matthias (2023)
At the center of the book lies the question concerning the relation between art and papal ceremonial in Rome during the pontificate of Paul V. (1605-1621). It is examined by focussing on the selected cases of the splendid ceremonial furnishings created for the canonisations of Francesca Romana and Carlo Borromeo at St. Peter's Basilica, as well as the Sala Regia in the Quirinal Palace. Using a multitude of textual and visual sources these works are reconstructed and put into the context for which they were created.